Medical Treatment of Rheumatoid Arthritis: A Review - Feroz, AHM (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i1.4641 J Bangladesh Coll Phys Surg 2010; 28: 30-39